Open Source Systems: Towards Robust Practices : 13th IFIP WG 2.13 International Conference, OSS 2017, Buenos Aires, Argentina, May 2223, 2017, proceedings /: 13th IFIP WG 2.13 International Conference, OSS 2017, Buenos Aires, Argentina, May 2223, 2017, proceedings. ([2017]) - Unknown
No abstract available